Venture Capital and Taxation - Abbott, Charles C.; Zuckert, Eugene M. (Quarterly Journal of Economics, 1941)
Journal Article Venture Capital and Taxation Get access Charles C. Abbott, Charles C. Abbott Harvard University Search for other works by this author on: Oxford Academic Google Scholar Eugene M. Zuckert Eugene M. Zuckert Graduate School of Business Administration Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 55, Issue 4, August 1941, Pages 667–682, https://doi.org/10.2307/1884123 Published: 01 August 1941